EVALUATION OF SLEMAN REGENCY PUBLIC SERVICE MALL PROJECT IMPLEMENTATION USING EARNED VALUE ANALYSIS METHOD - Andrean, Mochamad; Priyanto, Budi (Sean Institute, 2022)
Project execution does not always go according to plan. In its implementation, the construction of the Sleman Regency Public Service Mall experienced additional work and schedule changes according to the first Change Contac Order (CCO) with an overall contract value of Rp. 59,754,713,380.00 before VAT. To control and determine the performance of the project in terms of cost and cost, researchers use the earned value analysis method. The results of the Cost Variance (CV) study of Rp. 5,716,015,091 are positive and the Scheduel Variance (SV) value of Rp. 108,928,282 is positive. This means that the implementation of the project precedes the plan at a cost smaller than the plan. cost performance (CPI) of 1,428 and schedule performance (SPI) of 1,006. So that in the 20th week the project cost performance is better than the plan and the schedule performance is ahead of plan. The estimated value of the remaining time cost to complete the project (ETC) is Rp. 40,701,329,743 and the estimated total value at the end (EAC) is Rp. 54,038,698,289. The data provides information on the estimated cost of completing the project will be less than the budget value. an ETS value of 308,151 days and an EAS value of 448,151 days. This means that it is estimated to be completed quickly 2 days from the planned time of 450 calendar days.